Analisis Faktor Sosiodemografi Dalam Pengambilan Keputusan Pemilihan Tempat Persalinan Di Kabupaten Bangkalan - Uswatun Khasanah; Esyuananik Esyuananik; Anis Nurlaili (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract : Parents Factors, Decisions, Selection Of Delivery Places. Maternal and Infant Mortality Rate in Indonesia remains high. Approximately 95% of maternal deaths occur during labor due to obstetric complications. Efforts are made by doing delivery in health facilities so it does not happen late referred and handled and can be anticipated if maternity in health facilities. Factors that are considered to influence the decision of maternity selection by maternity mothers are socio-demographic factors, namely education & culture. High knowledge about health services causes individuals to tend to use health care facilities. This study aims to analyze the Sociodemografi Factors that Affect Decision Selection Place Birth to Maternity Mother. The research design using explanatory survey method with cross sectional design. This population are maternity mother in August-2016 with 51 samples of with multi stage sampling technique at coastal cluster, town and mountains, is Sepuluh health centers, Arosbaya health center and Galis health center. The data were taken by using quesioner and analized by Chi-Khuadrat. The results showed that the sociodemographic factor did not significantly influence the decision of maternity selection in maternal mother (p value>0,05). It is recommended that midwives further improve counseling in pregnant women in the third trimester related to preparing for the delivery process, among othersthrough.